Lingkungan Pendidikan Berbasis Hidden Curriculum dalam Pembentukan Karakter: Studi Kasus di Pondok Modern Darussalam Gontor Putra 1 Ponorogo Tahun Ajaran 2024-2025 M - Khotibul Umam; Bahrissalim Bahrissalim; Abdul Ghofur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Formal education often struggles with character formation due to fluctuating discipline, limited role modeling, and academic pressure. Pondok Modern Darussalam Gontor (PMDG) offers an alternative through a 24-hour hidden curriculum built on habituation, role modeling, institutional rituals, and peer norms. This study aims to describe the concept of the hidden-curriculum environment, analyze the role of teachers in character formation, and evaluate managerial strategies in its implementation. Using a qualitative single-case study and thematic analysis, data were collected through observation, interviews, and document review. Findings reveal six main channels of the hidden curriculum—daily rules, teacher exemplarity, institutional rituals, peer norms, structured reflection, and digital ethics—supporting a shift from sanction-based compliance to value internalization. The synergy of habituation, modeling, and reflection supported by measurable SOPs strengthens student character and offers an adaptable model for other pesantren.